Views on Hindu dharma - Gandhi, Mahatma, 1869-1948, author.
1 online resource
Keywords: "Mohandas Karamchand Gandhi took pride in calling himself a Sanatani Hindu. He lived by what he professed. Indeed, he spiritualized his entire political existence and his very opinion, world view and discourse was weighted with morality and ethics born of Hindu Dharma.This timely compilation of Mahatma Gandhi's views on Hindu Dharma is a remarkable and systematically arranged compendium of his ideas on every aspect of India's social and political life.Gandhi's views - disseminated through many short essays in Harijan and other journals of his time..."--Publisher.